2011
DOI: 10.1159/000324825
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Managing Fusiform Basilar Artery Aneurysms: From Acute Ischemic Stroke to a Massive Subarachnoid Hemorrhage

Abstract: We present the case of a patient with acute brain stem ischemic stroke who was found to have a fusiform basilar aneurysm with a thrombus within the dilated vessel. Three days after the ischemic stroke, the patient had a massive subarachnoid hemorrhage and died. This case illustrates the difficulties in the acute management of ischemic events in patients with basilar fusiform aneurysms, because the natural history of this disease encompasses both bleeding and thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moreover, all the above methods can only resolve the VBD-induced mass effect, and there is no convincing evidence to indicate that these methods can improve blood supply in the posterior circulation to prevent ischemic stroke in this territory. Some authors reported their trials with different kinds of stents and coils [24][25][26][27][28][29][30] to reconstruct the lumens of fusiform aneurysms of the basilar artery trunk, which may evolve from VBD 31 or combine with VBD. However, in those articles, reconstruction of the lumen might not have been long enough to cover the VBD because their targets were fusiform aneurysms and long-term follow-up evidence was not available, either, to support the effect of ischemic stroke prevention in the posterior circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all the above methods can only resolve the VBD-induced mass effect, and there is no convincing evidence to indicate that these methods can improve blood supply in the posterior circulation to prevent ischemic stroke in this territory. Some authors reported their trials with different kinds of stents and coils [24][25][26][27][28][29][30] to reconstruct the lumens of fusiform aneurysms of the basilar artery trunk, which may evolve from VBD 31 or combine with VBD. However, in those articles, reconstruction of the lumen might not have been long enough to cover the VBD because their targets were fusiform aneurysms and long-term follow-up evidence was not available, either, to support the effect of ischemic stroke prevention in the posterior circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Fusiform cerebral aneurysms can be divided into acute dissecting aneurysms and chronic fusiform or dolichoectatic aneurysms, which slowly enlarge and can be asymptomatic or associated with cranial nerve dysfunction, ischemic stroke, or subarachnoid hemorrhage [3, 4]. This distinction is often difficult even with advanced neuroimaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of perforating arteries with risk of brain stem infarctions is one of the major challenges facing the endovascular treatment of fusiform aneurysms of the basilar artery (BA) [6]. The overall prevalence of GIAs is higher in women than in men, and they tend to occur more frequently in the anterior circulation than in the posterior circulation [7].…”
Section: Introductionmentioning
confidence: 99%